Dampak Game Terhadap Anak Usia Dini - Edora Edora; Ahmad Turmudi Zy (DPPM Universitas Pelita Bangsa, 2022)
Digital technology changes many aspects of the daily life of Indonesian people, from socializing to education, from formal and informal matters to all involving digital technology, and this also involves all age groups, from early childhood to the elderly. There are also many digital games that are loved by all ages. The problem is the impact of digital-based games using mobile phones or tablets. Here the author focuses on research on the impact of digital games on an early age in terms of benefits on the growth and development of early childhood, in this paper some research from various parties who are competent in this research will be presented. those it can be concluded that there are positive and negative impacts of digital games (games) in early childhood. Keywords: Digital Technology, Game, Childhood, Impact.